Assessment of knowledge and skills of cardiopulmonary resuscitation among health workers at Nakuru County Referral Hospital - Manono, Betty K.; Mustisya, Albanus; Chakaya, Jackson (International Journal Of Community Medicine And Public Health, 2021)
Background: Cardiopulmonary resuscitation is critical in the emergency healthcare settings. Effective cardiopulmonary resuscitation improves the patients’ outcomes hence reducing mortality related to cardiac arrest. The aim of the study was to assess the knowledge and skills of cardiopulmonary resuscitation among health workers at Nakuru County Referral Hospital. Methods: The study adopted an analytic cross-sectional design. A census sampling technique was used to recruit respondents in the study. Questionnaires and checklists were used to collect data. Chi-square tests and multiple regression analysis were done to determine the significant association between demographic characteristics, knowledge and skills of cardiopulmonary resuscitation. Results: The study found that slightly above half 54.3% (n=88) of the respondents had low knowledge on cardiopulmonary resuscitation. Results revealed that age of respondent (p=0.038) and level of education (p=0.000) were significant. Cross tabulation showed that older respondents (>40 years) and those with a high level of education (degree and or masters) were more two and three times more likely to have a high knowledge of cardiopulmonary resuscitation. The study found out that majority 61.1% (n=99) of the respondents had poor CPR practice. Cross tabulation showed that respondents with high knowledge were four times (OR=4.303) more likely to have good practice. Conclusions: The study concluded that the performance of cardiopulmonary resuscitation is attributable to low CPR knowledge. The study recommends that more emphasis be placed on continuous professional development, and supervision be done after training to ensure that health workers follow the recommended guidelines.